Draft Annual Plan 1986-87 Volume X Medical and Public Health Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
This scheme is one of the centrally sponsored scheme and provision of funds is share on 50 : 50 basis between the state and centre. The department has so far implemented in 24 blocks of this Division out of which maintenance of cost of one block name Kotebalwal is devittel to the Non Plan Budget of the department and 23 blocks under Plan. No new block has been proposed to be covered in the 7th Plan. For maintenance of the scheme implemented in 23 blocks under Plan a provision to the tune of 9.33 lacs being 50% as state share has been proposed in the annual Plan 1986-87.
Planning and Development Department, Jammu and Kashmir Government